A novel Diameter-Selective functionalization of SWCNTs with lithium alkynylides - Gebhardt, Benjamin; Graupner, Ralf; Hauke, Frank; Hirsch, Andreas (European Journal of Organic Chemistry, 2010)
Covalent functionalization by addition to the sidewalls of single-walled carbon, nanotubes (SWCNTs) is one of the most important methods for the derivatization of carbon nanotubes. The nucleophilic addition of organometallic reagents (carbon- and nitrogen-based carbanions) has recently become a widely used tool for the introduction of functional moieties onto the surface of this new carbon allotrope. The extension, of this concept by the successful, nucleophilic addition of in situ generated lithium acetylides to the SWCNT scaffold is presented herein. The chemically derivatized SWCNTs have been characterized, in detail by TGA/MS, Raman, UV/Vis/NIR and fluorescence spectroscopy. On the basis of a detailed examination of the signals in the radial breathing-mode region of the Raman spectra, the preferred functionalization of smaller-diameter tubes has been clearly demonstrated. © 2010 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.